The role of Vit D and parathyroid hormone in clinical severity of patients with bipolar disorder. (13th April 2021) - Palummo, C.; Marone, L.; Caivano, V.; Vece, A.; Steardo, L.; Luciano, M.; Cerbo, A. Di; Vecchio, V. Del; Fiorillo, A.
Abstract : Introduction: Vitamin D modulates the biosynthesis of neurotransmitters and neurotrophic factors, thus influencing mood and its alterations. Decreased blood levels of Vitamin D are involved in many psychiatric disorders, in particular, affective disorders. As regards bipolar disorder (BD), an association between vitamin D deficiency and severity of illness has been found. Objectives: In this observational study, we assessed calcium homeostasis imbalance in a sample of patients with BD; in particular, we explored whether serum levels of PTH, Vitamin D and calcium influence the clinical presentation of BD and its symptom severity. Methods: All patients were administered with validated assessment instruments to assess psychopathology, affective temperaments and global functioning. Vitamin D and PTH levels were assessed in all patients. An-ad hoc schedule was administered for socio-demographic and clinical characteristics. Results: The total sample consisted of 199 patients (females: 51%; mean age: 47.1 ± 13.2 years). Levels of serum PTH were directly correlated with the total number of hospitalizations (p< 0.01), and of depressive (p< 0.0001), manic (p< 0.001) and hypomanic episodes (p< 0.01). Serum levels of Vitamin D were positively associated with age at first psychiatric contact and were inversely correlated with the total number of depressive episodes (p< 0.05) and cyclothymic temperament (p< 0.05). Conclusions: Increased levels of PTH and Vit D correlate with a worse clinical outcome of patients with BD. Our results highlight the importance to routinely assess PTH, Vit D and calcium levels in BD patients. Moreover, vitamin D may represent a valid add-on treatment for these patients. Disclosure: No significant relationships.